THE QURAN'S VERSES AND HADITHS IN NASIMI'S POETRY - Gülistan EKMEKÇİ (Fırat University, 2019)
Yunus Emre was a great poet who contributed to the creation of the love language by reflecting his sincerity on his poems, made a magnificent mark on Turkish literature thanks to this characteristic of him. Yunus Emre’s literary characteristics that were overshadowed by determining the Qur’an’s verses and hadiths in Yunus Emre’s Poetry will be studied. It is seen that Yunus Emre, engraining love to people, supported his messages with a